A Copula-VAR-X Approach for Industrial Production Modelling and Forecasting - Carluccio Bianchi; Alessandro Carta; Dean Fantazzini; Maria Elena De Giuli; Mario A. Maggi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
World economies, and especially European ones, have become strongly interconnected in the last decades and a joint modelling is required. We propose here the use of Copulas to build flexible multivariate distributions, since they allow for a rich dependence structure and more flexible marginal distributions that better fit the features of empirical data, such as leptokurtosis. We use our approach to forecast industrial production series in the core EMU countries and we provide evidence that the copula-VAR model outperforms or at worst compares similarly to normal VAR models, keeping the same computational tractability of the latter approach.
Keywords: C13; C32; C51; C53; 330; Forecasting; Industrial Production; Copulas; VAR models